The Integrating Technology in English Speaking Instruction : A Literature Review on Tools, Strategies, and Impact - Mislawiyadi Mislawiyadi; Sirrul Bari (JOEY: Journal of English Ibrahimy, 2025)
This literature review synthesizes empirical findings from national and international research on the integration of technology in English speaking instruction. The review identifies several categories of technological intervention, including mobile-assisted language learning (MALL), blended learning environments, AI-powered tools, gamification, and collaborative platforms. Studies show that these tools enhance speaking subskills—fluency, pronunciation, vocabulary, and grammar—while also increasing learner motivation, confidence, and engagement. For instance, 92–96% of learners reported improvements in vocabulary and fluency when using technology-enhanced instruction. Mobile-assisted learning showed measurable score gains in pronunciation (+10 points), fluency (+6), vocabulary (+6), and grammar (+4). A meta-analysis of 67 studies confirmed a statistically significant positive effect, with average learning gains exceeding 0.5 standard deviations (d = 0.51) over traditional methods. Additionally, learner engagement was found to account for 68.5% of the variance in speaking performance, demonstrating its central role in successful outcomes. While challenges remain—such as infrastructure limitations and unequal access—the evidence supports the pedagogical value of technology in making English speaking instruction more effective, interactive, and learner-centered.